Ongoing Alpha Activity in V1 Regulates Visually Driven Spiking Responses. (9th December 2015) - Dougherty, Kacie; Cox, Michele A.; Ninomiya, Taihei; Leopold, David A.; Maier, Alexander
Abstract: The interlaminar connections in the primate primary visual cortex (V1) are well described, as is the presence of ongoing alpha-range (7–14 Hz) fluctuations in this area. Less well understood is how these interlaminar connections and ongoing fluctuations contribute to the regulation of visual spiking responses. Here, we investigate the relationship between alpha fluctuations and spiking responses to visual stimuli across cortical layers. Using laminar probes in macaque V1, we show that neural firing couples with the phase of alpha fluctuations, and that magnitude of this coupling is particularly pronounced during visual stimulation. The strongest modulation of spiking activity was observed in layers 2/3. Alpha-spike coupling and current source density analysis pointed to an infragranular origin of the alpha fluctuations. Taken together, these results indicate that ongoing infragranular alpha-range fluctuations in V1 play a role in regulating columnar visual activity.